Stereotypes bias face perception via orbitofrontal–fusiform cortical interaction. Issue 3 (3rd December 2020) - Barnett, Benjamin O; Brooks, Jeffrey A; Freeman, Jonathan B
Abstract: Previous research has shown that social-conceptual associations, such as stereotypes, can influence the visual representation of faces and neural pattern responses in ventral temporal cortex (VTC) regions, such as the fusiform gyrus (FG). Current models suggest that this social-conceptual impact requires medial orbitofrontal cortex (mOFC) feedback signals during perception. Backward masking can disrupt such signals, as it is a technique known to reduce functional connectivity between VTC regions and regions outside VTC. During functional magnetic resonance imaging (fMRI), subjects passively viewed masked and unmasked faces, and following the scan, perceptual biases and stereotypical associations were assessed. Multi-voxel representations of faces across the VTC, and in the FG and mOFC, reflected stereotypically biased perceptions when faces were unmasked, but this effect was abolished when faces were masked. However, the VTC still retained the ability to process masked faces and was sensitive to their categorical distinctions. Functional connectivity analyses confirmed that masking disrupted mOFC–FG connectivity, which predicted a reduced impact of stereotypical associations in the FG. Taken together, our findings suggest that the biasing of face representations in line with stereotypical associations does not arise from intrinsic processing within the VTC and FG alone, but instead it depends in part on top-down feedback from the mOFC during perception.